Preparation of anti-CD4 monoclonal antibody-conjugated magnetic poly(glycidyl methacrylate) particles and their application on CD4+ lymphocyte separation - Pimpha N. (2014)
Novel immunomagnetic particles have been prepared for separation of CD4+ lymphocytes. The magnetic nanoparticles with a diameter of approximately 5-6 nm were first synthesized by co-precipitation from ferrous and ferric iron solutions and subsequently encapsulated with poly(glycidyl methacrylate) (PGMA) by precipitation polymerization. Monoclonal antibody specific to CD4 molecules expressed on CD4+ lymphocytes was conjugated to the surface of magnetic PGMA particles through covalent bonding between epoxide functional groups on the particle surface and primary amine groups of the antibodies. The generated immunomagnetic particles have successfully separated CD4+ lymphocytes from whole blood with over 95% purity. The results indicated that these particles can be employed for cell separation and provide a strong potential to be applied in various biomedical applications including diagnosis, and monitoring of human diseases. © 2010 Elsevier B.V. All rights reserved.